2012
DOI: 10.1111/ggi.12001
|View full text |Cite
|
Sign up to set email alerts
|

Trends of gender gaps in life expectancy in Japan, 1947–2010: Associations with gender mortality ratio and a social development index

Abstract: The increased trend of GGLE in Japan could be partly explained by increased disease-specific mortality ratios (male/female), especially those involving chronic bronchitis and emphysema, diseases of the liver, suicide and cancer. The recent decline of GGLE might imply that Japanese women have been catching up with the lifestyle of men, resulting in similar mortality patterns. This calls for gender-sensitive approaches to developing policies and programs that will help sustain healthy lifestyles to combat smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…In our previous study, we found that Japanese suicide gender mortality ratio (male: female) increased during the period of 1947-2010 (Liu et al, 2012). Japanese male suicide mortality rate has gradually increased during the twentieth century while Japanese female suicide rate has experienced the long-term stability with small fluctuations (Yamamura et al, 2006).…”
Section: Introductionmentioning
confidence: 91%
“…In our previous study, we found that Japanese suicide gender mortality ratio (male: female) increased during the period of 1947-2010 (Liu et al, 2012). Japanese male suicide mortality rate has gradually increased during the twentieth century while Japanese female suicide rate has experienced the long-term stability with small fluctuations (Yamamura et al, 2006).…”
Section: Introductionmentioning
confidence: 91%
“…We excluded 1,627 individuals who dropped out, leaving a total of 100,823 elderly individuals. Among them, 24,558 were already disabled with low-(5,920; 24.1%), middle-(10,166; 41.4%), and highlevel disabilities (8,392; 34.1%), and 80 (0.3%) had been certified as low-or middle-level disability in February or March, but not in April 2011. Thus, there were 76,265 elderly individuals that remained nondisabled on April 1, 2011.…”
Section: Subjectsmentioning
confidence: 99%
“…In Japan, 25% of citizens are over the age of 65 years, making it the world's first "super-aged society" [28]. Though the average life span of a Japanese woman is 86.5 years (ranking first in the world) and that of a Japanese man is 79.9 years (ranking fifth worldwide), the most important issue is healthy life expectancy, not the average life span.…”
Section: Agingmentioning
confidence: 99%